The Legal System for Professional Discipline of Medical Personnel: Constructing Justice and Dignity - Jaka Kusnanta Wahyuntara; Noor Saleh Ali Alzyoud; Majd Almanasra; Atik Nurfatmawati (Jurnal Hukum, 2025)
The medical professional discipline grants the Minister too broad authority to add types of disciplinary violations without clear boundaries. This study aims to analyze the regulation of the Minister of Health's role in the provisions regarding the medical professional discipline in Indonesia, which is currently not based on dignified justice. This study uses a socio-legal research approach. The results show that the regulation of the Minister of Health's role in the medical professional discipline is considered not based on dignified justice because it grants the Minister too broad authority to determine additional types of violations without adequate oversight mechanisms, thus creating legal uncertainty. Substantial, structural, and cultural weaknesses include the potential for unilateral expansion of norms, low competence of officials in the field of health law, and a culture that weakens social control. Therefore, reconstruction is needed by transferring the authority to determine types of violations from the Minister to an independent professional institution, following the Singaporean SMC model adapted to Indonesia's constitutional character, in order to build a more accountable, fair, and dignified disciplinary system.